Determining the Effectiveness of Sustainable Production Activities in Fishing Sector by Data Envelopment Analysis - Hülya Sayğı; Aysun Kop; Hatice Tekoğul; Burcu Taylan (Acta Natura et Scientia)
Data envelopment analysis is used when it is difficult to measure the relative effectiveness of organizational decision-making units due to a large number of similar inputs and outputs. Firstly, data envelopment analysis was discussed in this study. In this context, relative activities of 10 companies have been operating in fisheries sector for last nine years (2009-2017) which entered the Fortune 500 in Turkey and have sufficient data were measured using financial inputs and outputs. Relative effectiveness scores were obtained by examining the financial inputs and outputs of the companies that are in the Fortune 500 and operating in fisheries sector. In the second part of study, to reveal the technical efficiency and the ineffective ones resulting from the scale, DEA models including the input-oriented CCR (Charnes, Cooper, and Rhodes) and BCC (Banker, Charnes, and Cooper) model were established and the above mentioned procedures were repeated. Finally, it was investigated whether an investment system based on DEA could be established or not. DEA Frontier and DEA Solver software, one of the special software of DEA, was used for the solution of models using in data envelopment analysis. As a result of the study, the average efficacy percentage was found to be 88% for CCR and 93% for BCC. For the data obtained during 2009-2017, six companies were found to be active according to the CCR model, while seven companies were found to be effective according to the BCC model. Also, the targets were determined to activate the inactive companies.